Study on the interaction between ketoprofen and bovine serum albumin by molecular simulation and spectroscopic methods. Issue 6 (2011) - Zhu Zhu, Jin Lian Jin Lian; He He, Jia Jia; He He, Hua Hua; Tan Tan, Shu Hua Shu Hua; He He, Xiao Mei Xiao Mei; Pham-Huy Pham-Huy, Chuong Chuong; Li Li, Lun Lun
Abstract : The interaction between ketoprofen and bovine serum albumin (BSA) was investigated by molecular simulation, fluorescence and UV-vis spectroscopy methods under the simulated physiological conditions. Molecular simulation method performed to reveal the possible binding mode or mechanism suggested the binding forces between ketoprofen and BSA were mainly hydrophobic interaction and hydrogen bond, which was in agreement with the thermodynamic study (Δ H Φ and Δ S Φ were calculated to be 74.514 kJ/mol and 333.98 J/mol · K). The binding constants of ketoprofen and BSA at different temperatures (298, 310 and 318 K) were calculated according to the data obtained from fluorescence spectra and the results indicated that ketoprofen had strong ability to quench the intrinsic fluorescence of BSA via a combination of static and dynamic quenching. Meanwhile, the changes of the conformation of BSA caused by ketoprofen were qualitatively analyzed with the UV-vis and synchronous fluorescence spectroscopy. The distance between ketoprofen and tryptophan residue in BSA was calculated to be 1.58 nm.